Herbicides, Physiology of Action, and Safety 2015
DOI: 10.5772/61674
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Metabolism in Weeds — Selectivity and Herbicide Resistance

Abstract: The metabolic detoxication/bioactivation pathways, the levels and activity of enzymes, and endogenous cofactors mediating these reactions in crops have been well documented; however, much less evidence has been accumulated in weed species. The herbicide metabolism as a selectivity factor is summarized with special attention to acetyl-CoA carboxylases (ACCase)-inhibiting aryloxyphenoxypropionate, protoporphyrinogen IX oxidase (PPO) inhibitor, carotenoid biosynthesis inhibitor clomazone, and acetolactate synthas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Melting points were determined using an RT-2 melting apparatus (Shanghai PuZhe photoelectric Co., Shanghai, China) and were uncorrected. 1 H NMR and 13 C NMR spectra were obtained using a Bruker Avance 400 MHz spectrometer (Bruker Corporation, Switzerland). The chemical shift values (d) for the NMR spectra were reported as parts per million (ppm) using deuterated chloroform (CDCl 3 ), dimethyl sulfoxide (DMSO-d 6 ), or acetone-d 6 as the solvent and tetramethylsilane (TMS) as an internal reference standard.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melting points were determined using an RT-2 melting apparatus (Shanghai PuZhe photoelectric Co., Shanghai, China) and were uncorrected. 1 H NMR and 13 C NMR spectra were obtained using a Bruker Avance 400 MHz spectrometer (Bruker Corporation, Switzerland). The chemical shift values (d) for the NMR spectra were reported as parts per million (ppm) using deuterated chloroform (CDCl 3 ), dimethyl sulfoxide (DMSO-d 6 ), or acetone-d 6 as the solvent and tetramethylsilane (TMS) as an internal reference standard.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Sulfonylurea herbicides have been invented for nearly 40 years, and it is estimated that over 30 commercial products have been used globally for crop protection. , Although weed resistance to these families of herbicides due to overuse by farmers has become an inevitable concern, new sulfonylurea herbicides are continuously produced by clever modification based on structure–activity relationships. For example, monosulfuron, recently developed in China, is a special herbicide used for millet fields, where traditional sulfonylurea herbicides are harmful to millet and no other effective herbicides are available for this agricultural crop .…”
Section: Introductionmentioning
confidence: 99%
“…However, amino acid conjugates are less stable than sugar conjugates and can be reversed to form an active form of the parent herbicide compound (2,4-D) that is toxic (Sterling and Hall 1997). Jablonkai (2015) reported that in wheat, 2,4-D is primarily metabolized through aromatic-ring hydroxylation of the 2,4-dichloro-phenyl moiety, and an acidic aryl glycoside is subsequently formed by conjugation. Future investigations will be directed toward identification of 2,4-D metabolites in KCTR and wheat through the application of liquid chromatography-mass spectrometry techniques.…”
Section: Metabolism Of [ 14 C]24-d In Kctr Kss Mss Amaranthus Palmeri...mentioning
confidence: 99%
“…This result corresponds to the slow and mild development of poisoning symptoms until the end observation. [14] mentioned that structural barriers such as cuticles and cell walls get thicker with the age of weeds so that the penetration and translocation of glyphosate is reduced in the tissues, causing the active ingredients that reach the site of action not to be in lethal concentrations. To avoid the resistance of this weed after the application of glyphosate is interspersed with herbicides with different active ingredients.…”
Section: Table 2 the Development Of Symptoms Of Poisoning In E Indica...mentioning
confidence: 99%